Molecular structure and function of biological barriers - Krizbai, István A.; Fazakas, Csilla; Haskó, János; Molnár, Judit; Nyúl-Tóth, Ádám; Farkas, Attila E.; Wilhelm, Imola (Acta Biologica Szegediensis, 2015)
Biological barriers are indispensable for the integrity and function of many vertebrate organs. The barrier function is based on intercellular protein complexes of the plasma membrane which form paracellular diffusion barriers and separate internal and external fluid compartments, an indispensable prerequisite for every organ development and function. The review summarizes key characteristics and molecular structure of intercellular junctions (tight junctions and adherens junctions) responsible for cellular barrier formation. One of the most important such cellular barriers is the blood-brain barrier (BBB) which forms an active interface between the circulation and neural tissue. Its principal cellular components are cerebral endothelial cells, pericytes and astrocytes, whose finely tuned interactions are needed for a proper function. The review highlights the most important functions of the BBB including some novel regulatory aspects as well.